Development and Poverty: Critical Review of the Poverty Reduction Strategy Shift of Economic Growth to Empowerment - Musiyam, Muhammad (Forum Geografi, 1998)
There had been some changes of poverty preventation strategy for the government of the New Order. In the development process, the change of the strategy from economy growth method to the implementation of âPresidential Decree of Underdeveloped Territorial Program (IDT) âactually emphasized on the increased attention to the poor. It was proved that the combination of various programs could decrease the poverty rate both quantitatively and significantly. However, because the pattern of the top-down and the feature of the charity remained to dominate on the overall strategy, the poor could not have develop significantly independent. Thus, poverty preventation strategy in the future must emphasize on the development of the poorâs creativity, initiative, and capability based on the mobilization of the local resources, so it can make the poor develop and grow independently. In such a way, ontinual development will reasonably run. A change of strategy needs the reshuffle of political structure to democracy.